2004
DOI: 10.1007/s00210-004-0951-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterisation of the agonist radioligand binding site of 5-HT2A, 5-HT2B and 5-HT2C receptors

Abstract: In the present study we compared the affinity of various drugs for the high affinity "agonist-preferring" binding site of human recombinant 5-HT(2A), 5-HT(2B) and 5-HT(2C) receptors stably expressed in monoclonal mammalian cell lines. To ensure that the "agonist-preferring" conformation of the receptor was preferentially labelled in competition binding experiments, saturation analysis was conducted using antagonist and agonist radiolabels at each receptor. Antagonist radiolabels ([3H]-ketanserin for 5-HT(2A) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
161
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(177 citation statements)
references
References 48 publications
12
161
1
3
Order By: Relevance
“…In addition, a high concentration of SB206553 was required to block ā£-m5-HT action on 5-HT 2C -expressing cells, which suggests that 5-HT 2B is more sensitive to SB206553. The study by Knight et al (2004) had reported that 5-HT 2A antagonist, ketanserin, is also a potent blocker of the 5-HT 2C receptor. Ketanserin did not inhibit 5-HT-induced mechanical hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a high concentration of SB206553 was required to block ā£-m5-HT action on 5-HT 2C -expressing cells, which suggests that 5-HT 2B is more sensitive to SB206553. The study by Knight et al (2004) had reported that 5-HT 2A antagonist, ketanserin, is also a potent blocker of the 5-HT 2C receptor. Ketanserin did not inhibit 5-HT-induced mechanical hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…This concentration was chosen based on the membrane binding experiments where the signal to noise ratio was the strongest. Because the affinity of DOI for 5-HT 2C receptors is only about 10-fold greater than the affinity for the 2A site (Appel et al, 1990;Knight et al, 2004;McKenna et al, 1989a), we make the assumption that both 2A and 2C receptor density was being measured. Non-specific binding was defined in the presence of 10 uM ketanserin.…”
Section: [ 125 I]-doi Quantitative Autoradiographymentioning
confidence: 99%
“…6). Five cerulein injections in the control mice increased plasma amylase and lipase levels a These data were referred from two published reports (16,18). Fig.…”
Section: Effect Of Selective 5-ht 2a Antagonistsmentioning
confidence: 90%